Transformed Perturbation Solutions for Dynamic Stochastic General Equilibrium Models - Francisco Blasques; Marc Nientker (Tinbergen Institute, 2019)
This paper introduces a new solution method for Dynamic Stochastic General Equilibrium (DSGE) models that produces non explosive paths. The proposed solution method is as fast as standard perturbation methods and can be easily implemented in existing software packages like Dynare as it is obtained directly as a transformation of existing perturbation solutions proposed by Judd and Guu (1997) and Schmitt-Grohe and Uribe (2004), among others. The transformed perturbation method shares the same advantageous function approximation properties as standard higher order perturbation methods and, in contrast to those methods, generates stable sample paths that are stationary, geometrically ergodic and absolutely regular. Additionally, moments are shown to be bounded. The method is an alternative to the pruning method as proposed in Kim et al. (2008). The advantages of our approach are that, unlike pruning, it does not need to sacrifice accuracy around the steady state by ignoring higher order effects and it delivers a policy function. Moreover, the newly proposed solution is always more accurate globally than standard perturbation methods. We demonstrate the superior accuracy of our method in a range of examples.
Keywords: C15; C63; E00; 330; Higher-order perturbation approximation; non-explosive simulations; stochastic stability